A new species of Melobasina (Ulaikoilia Bílý & Kubáň) (Coleoptera: Buprestidae) from Sulawesi - Levey, Brian (Zootaxa, 2015)
A new species Melobasina (Ulaikoilia) jennyae sp. n. (Coleoptera: Buprestidae) is described from Sulawesi, Indonesia. A key is provided to distinguish the new species from the other two known species.